The Effect of Leverage, Liquidity, Capital Structure, Company Size, and Sales Growth on Financial Performance (A Study of Basic Materials Companies Listed on the Indonesia Stock Exchange for the Period 2020-2024) - Dini Zaskya; Mukhzarudfa; Muhammad Ridwan (Greenation International Journal of Economics and Accounting, 2025)
The purpose of this study is to examine and analyze the effect of leverage, liquidity, capital structure, company size, and sales growth on financial performance. The population used is basic materials companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Sampling was conducted using purposive sampling based on predetermined criteria. The method used was quantitative, using secondary data in the form of companies' annual financial reports. The sample in this study consisted of 59 companies, and the observation period was from 2020 to 2024. The findings of this study indicate that leverage, liquidity, and capital structure have a negative effect on financial performance. Meanwhile, company size and sales growth have a positive effect on financial performance.